Parole de queerzine : archive_corps_technologie - Thérèse Courau (Itinéraires)
This article analyse some features and issues of the new post-feminist semiotics related to the development of queer blogzines on Web 2.0 that function as powerful counter-technologies of gender in the production of new post-identity subjectivities. To this end, we consider the case of the queerzine Parole de Queer, originally distributed in paper format in Catalan cities such as Barcelona or Valencia, but mainly relayed and enriched by digital distribution, thanks to the blog and the social networks associated with the zine. Defined by Paul Beatriz Preciado as a “real-time archive of the action and productions of sexual and gender minorities,” the aim is to analyse how this medium functions as a speech_body_technology interface that supports queer politics of viral proliferation of new representations of gender, sexuality and post-organic bodies. Representations that play on the fluidity and plurisemioticity of the numeric universe.